The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2174/22113626130107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in the Anti-Inflammatory Properties of Native and Genetically Engineered Lactic Acid Bacteria

Abstract: Lactic acid bacteria (LAB) represent a heterogeneous group of microorganisms that have been shown to possess therapeutic properties since they are able to prevent the development of some diseases, as shown mostly on animal models for cancer, infections and gastrointestinal disorders such as intestinal inflammation. LAB have been shown to regulate mucosal immune responses by modulating the production and liberation of regulatory agents such as cytokines by the host. Some of these cytokines, such as the anti-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…Anti-oxidative effect of probiotics may be an important mechanism involved in its function such as antiin ammatory response because both local and systemic in ammatory responses are associated with the production of ROS. In line with the review by LeBlanc et al [ 51 ], which indicated antioxidant enzymes (such as CAT and SOD) produced by lactic acid bacteria could eliminate ROS and modulate the release of host cytokines (such as IL-10), and alleviate the severity of intestinal in ammatory diseases. Furthermore, a study con rmed that L. plantarum C88 could block alcohol-induced chronic and acute liver damage by improving intestinal barrier dysfunction, inhibiting intestinal endotoxin-mediated in ammation, and ameliorating oxidative stress [ 52 ].…”
Section: Probiotic Strains Have Been Shown To Stimulate Dendritic Cell-induced T-regulatory Cells To Attenuate Il-6supporting
confidence: 79%
“…Anti-oxidative effect of probiotics may be an important mechanism involved in its function such as antiin ammatory response because both local and systemic in ammatory responses are associated with the production of ROS. In line with the review by LeBlanc et al [ 51 ], which indicated antioxidant enzymes (such as CAT and SOD) produced by lactic acid bacteria could eliminate ROS and modulate the release of host cytokines (such as IL-10), and alleviate the severity of intestinal in ammatory diseases. Furthermore, a study con rmed that L. plantarum C88 could block alcohol-induced chronic and acute liver damage by improving intestinal barrier dysfunction, inhibiting intestinal endotoxin-mediated in ammation, and ameliorating oxidative stress [ 52 ].…”
Section: Probiotic Strains Have Been Shown To Stimulate Dendritic Cell-induced T-regulatory Cells To Attenuate Il-6supporting
confidence: 79%
“…Lactic acid bacteria (LAB) regulated mucosal immune responses by modulating the production and liberation of host cytokines. LABs have been shown to regulate inflammatory immune responses by increasing the concentration of IL‐10, in order to prevent certain inflammatory diseases . Our previous study has shown that nisin regulated neurochemicals and cecal microflora imbalance in mice .…”
Section: Introductionmentioning
confidence: 96%
“…In particular, probiotics represent a potential alternative for IBD treatment due to their active role in enhancing the intestinal barrier function, by either modifying the intestinal microbiota or modulating the host immune response (3,4). Notably, it has been previously shown that a yogurt prepared with a pool of candidate probiotic strains of Lactobacillus delbrueckii subsp.…”
mentioning
confidence: 99%